2014
DOI: 10.1007/s10482-014-0305-2
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization, antioxidant activity and anti-aging of exopolysaccharides by Flammulina velutipes SF-06

Abstract: The main objective of this work was to purify the exopolysaccharides (EPS) of Flammulina velutipes SF-06 and investigate the relationship between the different purified fractions and bioactive activity. Two fractions (EPS-1 and EPS-2) were separated and purified by DEAE-52 cellulose and Sephadex G-100 cellulose column chromatography. Monosaccharides composition analysis by gas chromatography indicated that EPS, EPS-1 and EPS-2 were heteropolysaccharides in which rhamnose was a major component. Fourier transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
1
20
0
2
Order By: Relevance
“…In the present study, EPS and DEPS displayed remarkable reducing power and scavenging capacity towards the DPPH, hydroxyl and superoxide anion radicals, indicating that both EPS and DEPS possessed potential antioxidant activity. Compared with other reports, DEPS also showed an antioxidant capacity superior to the same concentrations of EIPS (enzymatic intracellular polysaccharides), IPS (intracellular polysaccharides) and EPS from Flammulina velutipes 15, 23 . Based on these results, DEPS extracted from T .…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…In the present study, EPS and DEPS displayed remarkable reducing power and scavenging capacity towards the DPPH, hydroxyl and superoxide anion radicals, indicating that both EPS and DEPS possessed potential antioxidant activity. Compared with other reports, DEPS also showed an antioxidant capacity superior to the same concentrations of EIPS (enzymatic intracellular polysaccharides), IPS (intracellular polysaccharides) and EPS from Flammulina velutipes 15, 23 . Based on these results, DEPS extracted from T .…”
Section: Discussionmentioning
confidence: 46%
“…The major components of EPS and DEPS were mannose, galactose and glucose, which were different from the monosaccharide compositions of other EPS from F . velutipes 15 and Hericium erinaceus 16 , possibly due to differences in the culture medium, strains, fermentation conditions and extraction conditions. Furthermore, rhamnose was detected only in DEPS, indicating that rhamnose may have important contributions to the antioxidant activities of polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…SOD protects cells from being damaged by superoxide anion radicals by converting them to hydrogen peroxide, a less active free radical (Siu et al, 2013). In another study, exopolysaccharides (EPS) from F. velutipes were purified and characterized and it was found that the purified fractions were mainly composed of rhamnose (Ma et al, 2015a). Similarly, these EPS fractions were shown to exhibit potent antioxidant activity in vitro such as reducing power and the scavenging capability of hydroxyl, DPPH and superoxide anions (Ma et al, 2015a).…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…In another study, exopolysaccharides (EPS) from F. velutipes were purified and characterized and it was found that the purified fractions were mainly composed of rhamnose (Ma et al, 2015a). Similarly, these EPS fractions were shown to exhibit potent antioxidant activity in vitro such as reducing power and the scavenging capability of hydroxyl, DPPH and superoxide anions (Ma et al, 2015a). This study also demonstrated the purified EPS fractions stimulated anti-aging activity in mice as evidenced by the increased catalase level and decreased malondialdehye content in the organs of the mice.…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…Analizę właściwości antyoksydacyjnych przeprowadzono za pomocą nieznacznie zmodyfikowanej metody z użyciem odczynnika DPPH opisanej przez Molyneuxa, Abderrahima i wsp., Ma i wsp., Regulską i Samsonowicza [17,18,19,20]. W przypadku oznaczeń dotyczących DPPH materiałem odnie sienia był etanolowy roztwór troloksu.…”
Section: Materiały I Metodyunclassified